Influence of Heat Treatment on Spatial Distribution of Chemical Elements in Welding Microalloyed Steels - Tkachenko, I.F.; Uniyat, M.A. (Металлофизика и новейшие технологии, 2015)
The effect of isothermal holding of various duration at subcritical temperature on the spatial distribution of main chemical elements in the finally normalized X60, E36, and ASTM A516-65 steels is studied using SEM X-ray microanalysis. Based on results of statistical processing of the local concentrations’ measurements, a quantitative characteristic for inhomogeneity of distribution is proposed. As revealed, the most uniform distribution of the elements is achieved after holding at (710±5)°С during 1—2 hours for X60 and ASTM A516-55 steels, and 4 hours for E36 steel. The obtained results are in agreement with the change in steels microstructure caused by the mentioned heat treatment.